2022
DOI: 10.1038/s41418-022-01009-9
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondria supply sub-lethal signals for cytokine secretion and DNA-damage in H. pylori infection

Abstract: The bacterium Helicobacter pylori induces gastric inflammation and predisposes to cancer. H. pylori-infected epithelial cells secrete cytokines and chemokines and undergo DNA-damage. We show that the host cell’s mitochondrial apoptosis system contributes to cytokine secretion and DNA-damage in the absence of cell death. H. pylori induced secretion of cytokines/chemokines from epithelial cells, dependent on the mitochondrial apoptosis machinery. A signalling step was identified in the release of mitochondrial S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Similarly, chronic low-grade inflammation generally contributes to oncogenesis and tumour progression 7 , and at least in some scenarios this is initiated by mitochondrial dysfunction 193 196 . Finally, SMAC release upon minority MOMP driven by Helicobacter pylori seems to have a role in both the short-term and the long-term detrimental effects of the infection as it drives pathogenic inflammation as well as DNA damage in the absence of overt RCD, ultimately promoting malignant transformation 197 .…”
Section: Mtdamp Signalling In Diseasementioning
confidence: 99%
“…Similarly, chronic low-grade inflammation generally contributes to oncogenesis and tumour progression 7 , and at least in some scenarios this is initiated by mitochondrial dysfunction 193 196 . Finally, SMAC release upon minority MOMP driven by Helicobacter pylori seems to have a role in both the short-term and the long-term detrimental effects of the infection as it drives pathogenic inflammation as well as DNA damage in the absence of overt RCD, ultimately promoting malignant transformation 197 .…”
Section: Mtdamp Signalling In Diseasementioning
confidence: 99%
“…During minority MOMP caspase activity is generally not high enough to induce cell death, raising the question if there is a threshold for caspase activity in blocking inflammatory signalling pathways. Recently, three separate studies observed increased inflammation upon the induction of minority MOMP [73,106,107]. Pathogenic infections can induce minority MOMP causing caspase-dependent DNA damage and the secretion of pro-inflammatory cytokines [106,107].…”
Section: Minority Momp: Can Sublethal Caspase Activity Block Momp-ind...mentioning
confidence: 99%
“…Recently, three separate studies observed increased inflammation upon the induction of minority MOMP [73,106,107]. Pathogenic infections can induce minority MOMP causing caspase-dependent DNA damage and the secretion of pro-inflammatory cytokines [106,107]. Furthermore, induction of type I interferons was observed upon minority MOMP caused by the formation of mtDNA double strand breaks.…”
Section: Minority Momp: Can Sublethal Caspase Activity Block Momp-ind...mentioning
confidence: 99%
“…Consistently, blocking caspase activity following mitochondria outer membrane permeabilization (MOMP), the central mechanism of intrinsic apoptosis (see Box 2), stimulates Type I IFN response and NF‐κB activation thus promoting immune responses, without ultimately preventing killing. Notably, inflammation can also ensue under conditions of so‐called minority MOMP, which is insufficient to fully activate caspase signaling 153–155 . Whether the strength of (MOMP‐induced) caspase signaling ultimately determines its contextual role in regulating inflammation during ICD remains speculative.…”
Section: Defining the Immunogenic Cell Death Code: Constitutive And I...mentioning
confidence: 99%
“…Notably, inflammation can also ensue under conditions of so-called minority MOMP, which is insufficient to fully activate caspase signaling. [153][154][155] Whether the strength of (MOMP-induced) caspase signaling ultimately determines its contextual role in regulating inflammation during ICD remains speculative. Furthermore, caspase-8 has a scaffolding function driving the assembly of a complex together with Fas-associated death domain (FADD) and RIPK1 ripoptosome, which promotes NF-κB activation and chemokine production after ER stress-mediated TRAIL stimulation.…”
Section: Breaking Down the Dogma: Immunogenic Apoptosismentioning
confidence: 99%